2011
DOI: 10.17221/148/2011-pse
|View full text |Cite
|
Sign up to set email alerts
|

Induced-phytoextraction of heavy metals from contaminated soil irrigated by industrial wastewater with Marvel of Peru (Mirabilis jalapa L.)

Abstract: The primary objective of this study was to evaluate the effect of ethylene diamine tetraacetic acid (EDTA) and citric acid (CA) on Mirabilis jalapa L. growth and phytoextraction of heavy metals from the multi-metal contaminated soil. The results showed that the application of CA (5 and 8 mmol/kg) and EDTA (5 mmol/kg) increased plant growth, while when the concentration of EDTA was up to 8 mmol/kg, the shoot biomass significantly decreased relative to the control plants (P < 0.05); it suffered 48.1%, 53.1%, 58.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The maximum concentration of Cd we found was 60 mg kg −1 in the M. jalapa leaves. We also confirmed the findings highlighted by Sun et al (2011) that M. jalapa is able to uptake Cd and Cu; in fact, we found a PU of 12.72 % for Cu. In agreement with Cao et al (2007), we observed the ability of M. jalapa to accumulate Pb in the rhizosphere, even though the leaves uptake for this metal was the lowest (0.73 %).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The maximum concentration of Cd we found was 60 mg kg −1 in the M. jalapa leaves. We also confirmed the findings highlighted by Sun et al (2011) that M. jalapa is able to uptake Cd and Cu; in fact, we found a PU of 12.72 % for Cu. In agreement with Cao et al (2007), we observed the ability of M. jalapa to accumulate Pb in the rhizosphere, even though the leaves uptake for this metal was the lowest (0.73 %).…”
Section: Discussionsupporting
confidence: 91%
“…It is also well known for its rapid growth and metal hyperaccumulation properties (Kambhampati and Williams 2001;Cao et al 2007;Yu and Zhou 2009;Sun et al 2011). Hyperaccumulation of heavy metals by some terrestrial plants has been extensively investigated.…”
mentioning
confidence: 99%
“…Rice on these soils can contain up to 3 mg kg À1 of Cd, exceeding the World Health Organization's recommendations of less than 0.2 mg kg À1 (Schnoor, 2004). For example, in the SZIAs (China), the concentration of Cd in surface soil (0e20 cm) was 5.12 AE 0.19 mg kg À1 , which is 5.1 times higher than the corresponding environmental quality standard (Grade III) (1.0 mg kg À1 ) for Cd in soils of China (GB 15618-1995) (Sun et al, 2011b). Accordingly, Wu et al (1989) reported that the Cd concentrations at Sluice Gate I in the Zhangshi irrigation areas ranged from 5 to 7 mg kg À1 .…”
Section: Article In Pressmentioning
confidence: 90%
“…For example, Chen and Cutright (2002) reported that EDTA increased the shoot concentration of Cd from 34.2 mg kg À1 to 115 mg kg À1 in sunflower. In the presence of 1 mg kg À1 EDTA, Cd accumulation and translocation from root to the shoot of R. globosa increased by 155% (Sun et al, 2011a). Phytoextraction with water spinach and EDDS/NTA was feasible in the soil with 2.5 mg Cd kg À1 ; both EDDS and NTA enhanced the accumulation of Cd in roots and shoots of water spinach, and NTA was more effective than EDDS.…”
Section: Chelators and Hormonesmentioning
confidence: 95%
“…The main disadvantages of the method are very low effi ciency of Cu phytoextraction and side-effects, particularly the inevitable hazard to groundwater arising when the chelating agents are applied at rates high enough to radically increase Cu uptake by plants. Many papers that appear nowadays, however, obstinately continue to emphasize mainly the positive aspects of this method (Ciura et al 2005 ;Sun et al 2011 ;Smolińska and Król 2012 ;Ali et al 2013 ).…”
Section: Chemically Assisted Phytoextractionmentioning
confidence: 99%